Aerodynamic Comparison of Conventional and Bioinspired Turbines for Enhanced Wind Energy Applications in Low Wind Conditions - Quesada-Bedoya Luis Felipe; Lebrun-Llano David; Espitia-Mesa Gabriel; Tamayo-Avendaño Jorge Mario; Osorio-Gómez Gilberto (E3S Web of Conferences)
Wind energy is projected to account for 35% of global production by 2050, with a significant contribution from large wind farms located in high-wind-speed areas. However, in low-wind regions, it is necessary to adapt turbines to maximize efficiency. This has led to the development of blades based on biomimetic principles, which improve performance in such conditions. To validate this approach, a comparative aerodynamic analysis is proposed between a conventional and a bio-inspired turbine. The proposed methodology involves using Computational Fluid Dynamics (CFD) simulations and Blade Element Momentum Theory (BEMT) to predict the behavior of both designs. Variables such as power coefficients (Cp), thrust (Ct), axial force, and torque are evaluated, comparing the performance of the rotors under identical conditions. The goal is to determine the feasibility of bio-inspired turbines and their adaptation to horizontal-axis wind turbines at low wind speeds, starting from 2.5 m/s. The results, validated in CFD and BEMT simulations, show that bio-inspired turbines have up to 33% higher performance compared to conventional rotors, highlighting their potential to improve wind energy efficiency under adverse environmental conditions, especially in regions where wind speeds are low or inconsistent. This demonstrates the viability of bio-inspired designs in enhancing renewable energy technologies.